Olfaction in patients with suspected parkinsonism and scans without evidence of dopaminergic deficit (SWEDDs). Issue 7 (9th March 2009) - Silveira-Moriyama, L; Schwingenschuh, P; O'Donnell, A; Schneider, S A; Mir, P; Carrillo, F; Terranova, C; Petrie, A; Grosset, D G; Quinn, N P; Bhatia, K P; Lees, A J
Abstract : Background: Positron emission tomography and single photon emission computed tomography scanning have 87–94% sensitivity and 80–100% specificity to differentiate patients with Parkinson's disease (PD) from control subjects and patients with essential (ET) or atypical tremor. More than 10% of patients diagnosed as early PD can have scans without evidence of dopaminergic deficiency (SWEDDs). This study investigated whether smell tests can help identify possible cases with SWEDDs. Methods: The 40 item University of Pennsylvania Smell Test (UPSIT) was used to evaluate the sense of smell in 21 SWEDDs patients. Twenty-six ET patients, 16 patients with a diagnosis of idiopathic adult onset dystonia (D), 191 non-demented PD patients and 136 control subjects were also tested. Multiple regression analyses were used to compare the mean UPSIT score in the SWEDDs group with the other four groups (ET, D, PD and controls) after adjusting for the effects of relevant covariates. Results: The mean UPSIT score for the SWEDDs group was greater than in the PD group (p<0.001) and not different from the mean UPSIT in the control (p = 0.7), ET (p = 0.4) or D (p = 0.9) groups. Smell tests indicated a high probability of PD in only 23.8% of SWEDDs as opposed to 85.3% of PD patients. Conclusions: In a patient with suspected PD, a high PD probability on smell testing favours the diagnosis of PD, and a low PD probability strengthens the indication for dopamine transporter imaging.